2015
DOI: 10.1002/pon.3769
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation group intervention for breast cancer survivors: results of a randomized clinical trial

Abstract: BCS in the CR group showed immediate and sustained improvements in self-reported cognitive complaints and memory functioning on neurocognitive testing. Results of the qEEG substudy provide some support for neurophysiological changes underlying the intervention. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 31 publications
2
75
0
2
Order By: Relevance
“…[7] Another implication of the results is that routine cognitive assessment of older survivors undergoing hormonal therapy might be used to identify those in need of interventions like medication reminders or supportive care, or to identify those who might be considered for alternative regimens with fewer cognitive side effects. If any medication-induced cognitive changes are identified, promising evidence suggests that compensatory cognitive rehabilitation strategies [51, 52] may be effective in improving cognitive function and potentially promoting treatment adherence. Additionally, interventions that include physical activity can mitigate cognitive impairment and other treatment side effects, [53] and could be examined as methods to enhance hormonal therapy completion.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Another implication of the results is that routine cognitive assessment of older survivors undergoing hormonal therapy might be used to identify those in need of interventions like medication reminders or supportive care, or to identify those who might be considered for alternative regimens with fewer cognitive side effects. If any medication-induced cognitive changes are identified, promising evidence suggests that compensatory cognitive rehabilitation strategies [51, 52] may be effective in improving cognitive function and potentially promoting treatment adherence. Additionally, interventions that include physical activity can mitigate cognitive impairment and other treatment side effects, [53] and could be examined as methods to enhance hormonal therapy completion.…”
Section: Discussionmentioning
confidence: 99%
“…The premise of restoration-based methods is that through repetitive practice of cognitive retraining activities, overall cognitive performance will improve [21]. Recent clinical studies evaluating the use of restoration-based methods with cancer survivors, including breast cancer survivors, has found that these methods can improve cognitive function [22,23]. Unfortunately, these studies and several others suggest that this restoration approach has little impact on everyday life performance [2226].…”
Section: Introductionmentioning
confidence: 99%
“…Since complaints are inextricably tied to mood and psychological processes, they can signal coincident mood symptoms. Effective intervention approaches may include cognitive rehabilitation [19], and Cognitive Behavioral Therapy [35] such as addressing harmful or negative thought patterns, and cognitive complaints may be the best measures to assess intervention efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The Cognitive Rehabilitation Study sample (n=72) consisted of female breast cancer survivors with persistent cognitive complaints following primary treatment for cancer recruited for two separate clinical trials of a cognitive remediation protocol [18, 19]. Baseline data were used in the current study.…”
Section: Methodsmentioning
confidence: 99%